Predictive role of microvesicles in cirrhotic patients: A promised land or a land of confusion? A narrative review - Andrea Boccatonda; Fabio Piscaglia (Annals of Hepatology)
Mammalian cells release several membrane-enclosed vesicles called extracellular vesicles. Those vesicles can contain several molecules such as proteins, DNA and various RNA. Therefore, extracellular vesicles can act as a target delivery system and exert multiple biological effects. Several works demonstrated that extracellular vesicles are increased or dysregulated in patients with cirrhosis, and they can be predictive of disease progression, complications and mortality. This review aims to summarize and highlight the role of extracellular vesicles in the cirrhotic patient and how they correlate with the degree of disease and with complications, particularly with the development of portal thrombosis and hepatocellular carcinoma.